A German translation and validation of the sense of agency scale - Bart, Victoria K. E.; Wenke, Dorit; Rieger, Martina (Frontiers in Psychology, 2023)
Sense of agency refers to the experience of controlling one’s actions and through them events in the outside world. General agency beliefs can be measured with the Sense of Agency Scale (SoAS), which was originally developed by Tapal et al. (2017) and consists of the sense of positive agency subscale (i.e., feeling of being in control over one’s own body, mind, and environment) and the sense of negative agency subscale (i.e., feeling existentially helpless). The aim of the present study was to validate a German version of the SoAS. Using factor analyses, we replicated the two-factor structure of the original version of the SoAS. Further, the German SoAS showed good model fits, good internal consistency, and moderate test-retest reliability. Construct validity was supported by significant low to moderate correlations of the German SoAS with other conceptually similar, but still distinct constructs such as general self-efficacy. Additionally, the German SoAS has an incremental value in explaining variance in the extent of subclinical symptoms of schizotypal personality disorder that goes beyond variance explained by constructs that are conceptually similar to sense of agency. Taken together, the results indicate that the German SoAS is a valid and suitable instrument to assess one’s general agency beliefs.